THE EFFECTIVENESS OF RME AND SCIENTIFIC APPROACHES IN TERMS OF MATHEMATICAL LITERACY AND LEARNING INTEREST - Shinta Bella Margaretta; Sri Andayani; Wahyu Setyaningrum (UNIVERSITAS MUHAMMADIYAH METRO, 2026)
AbstractStudents’ low levels of mathematical literacy and learning interest indicate a need for effective instructional approaches that can address both cognitive and affective learning outcomes. Comparative studies on the effectiveness of the RME and scientific approaches in improving mathematical literacy and learning interest remain limited, especially at the SMP level. This study examines the effectiveness of each approach and compares their impact on students’ mathematical literacy and learning interest. This study employed a quantitative approach using a pretest–posttest control group design. The population of the study consisted of all seventh-grade students at a public SMP in Yogyakarta. The sample comprised 64 students from two seventh-grade classes. The participants were selected using convenience sampling. The experimental group received RME-based instruction, while the control group was taught using the scientific approach. MANOVA results show that both approaches significantly improve mathematical literacy and learning interest. However, no significant difference was found between the two groups, as indicated by a p-value > 0.05. These findings suggest that both approaches are equally effective. The study provides insight for teachers in applying context-based learning. Future research may explore digital-based strategies to further support mathematical literacy and learning interest.Â AbstrakRendahnya tingkat literasi matematika dan minat belajar siswa menunjukkan perlunya pendekatan yang efektif untuk mengembangkan hasil belajar kognitif maupun afektif. Penelitian komparatif mengenai efektivitas pendekatan RME dan pendekatan saintifik dalam meningkatkan literasi matematika dan minat belajar masih terbatas, khususnya di tingkat SMP. Penelitian ini bertujuan mengkaji efektivitas masing-masing pendekatan dan membandingkan pengaruhnya terhadap literasi matematika dan minat belajar siswa. Penelitian ini menggunakan pendekatan kuantitatif dengan desain pretest–posttest kelompok kontrol. Populasi penelitian terdiri atas seluruh siswa kelas VII di salah satu SMP negeri di Yogyakarta. Sampel penelitian berjumlah 64 siswa yang berasal dari dua kelas VII. Partisipan dipilih menggunakan teknik convenience sampling. Kelompok eksperimen diajar dengan pendekatan RME, sedangkan kelompok kontrol menggunakan pendekatan saintifik. Hasil analisis MANOVA menunjukkan bahwa kedua pendekatan efektif dalam meningkatkan literasi matematika dan minat belajar siswa. Namun, tidak terdapat perbedaan signifikan antara kedua kelompok (nilai p > 0.05), yang berarti keduanya memiliki efektivitas yang setara. Temuan ini memberikan wawasan bagi guru dalam menerapkan pembelajaran berbasis konteks. Penelitian lanjutan dapat mengeksplorasi integrasi teknologi untuk mendukung pengembangan literasi matematika dan minat belajar.